2012
DOI: 10.1016/j.bone.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived heparan sulfate potentiates the osteogenic activity of bone morphogenetic protein-2 (BMP-2)

Abstract: Lowering the efficacious dose of bone morphogenetic protein-2 (BMP-2) for the repair of critical-sized bone defects is highly desirable, as supra-physiological amounts of BMP-2 have an increased risk of side effects and a greater economic burden for the healthcare system. To address this need, we explored the use of heparan sulfate (HS), a structural analog of heparin, to enhance BMP-2 activity. We demonstrate that HS isolated from a bone marrow stromal cell line (HS5) and heparin each enhances BMP-2-induced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
100
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 65 publications
10
100
2
Order By: Relevance
“…the osteogenic effects is complex, mainly owing to the reversible, noncovalent interactions between heparin and heparin-binding GFs, which ensure minimal impact on GF structure. 13,30,37,39,43,44,[48][49][50][51][52] We demonstrated that the nanocomplexes in our study not only effectively loaded and sustained release of PlGF-2/BMP-2, but also maintained their bioactivities for bone regeneration. A key result in this study was the bioactivity of the released PlGF-2 being comparable to that of the released BMP-2, despite its dose being half that of BMP-2.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…the osteogenic effects is complex, mainly owing to the reversible, noncovalent interactions between heparin and heparin-binding GFs, which ensure minimal impact on GF structure. 13,30,37,39,43,44,[48][49][50][51][52] We demonstrated that the nanocomplexes in our study not only effectively loaded and sustained release of PlGF-2/BMP-2, but also maintained their bioactivities for bone regeneration. A key result in this study was the bioactivity of the released PlGF-2 being comparable to that of the released BMP-2, despite its dose being half that of BMP-2.…”
supporting
confidence: 52%
“…38,39,43 Also, Martino et al 40 showed that domain II (Fg β15-66 (2) ) of heparin exhibits high affinity for GFs in general, but with heparin displaying a fourfold stronger affinity for PlGF-2 than for BMP-2; 44 they also revealed a specific heparin-binding portion of PlGF-2 spanning residues 123-144 and having the sequence RRPKGRGKRRREKQRPTDCHL. 44 However, in our study, the difference of loading efficiency between PlGF-2 and BMP-2 was not so prominent, perhaps because both GFs were applied at overall low doses and exhibited high affinity to heparin.…”
mentioning
confidence: 99%
“…We also showed that exogenous heparin dosedependently inhibited BMP6-mediated ectopic bone formation in rats which is in contrast to previous results showing that heparin potentiates BMP2 osteogenic activity [50,53]. These differences are consistent with in vitro data, showing that heparin influences the activity of various BMPs differently [15,30,50].…”
Section: Discussionsupporting
confidence: 86%
“…[62] Heparin sulfate, which is less negatively charged and which shows less generalized affinity than heparin, has been used to mitigate this problem with BMP-2. [63] More interestingly, this effect has also been specifically used to improve therapeutic outcomes. A customized heparin hydrogel system was designed for maximal binding of inflammatory cytokines, which inhibit wound healing, and was shown to outperform the commercial Promogran product in reducing inflammation and promoting wound healing in mice.…”
Section: Immobilization Of Drugs In Hydrogelsmentioning
confidence: 99%